Spectral broadening of radially polarized pulses through a gas-filled hollow-core fiber. (15th April 2019) - Zhao, Ruirui; Qiao, Lingling; Wang, Ding; Zhao, Yu; Leng, Yuxin; Li, Ruxin
Highlights: Experiment for radially polarized pulses through noble gas-filled hollow-core fibers. A radially polarized supercontinuum covering from 540 nm to 1070 nm is obtained. The supercontinuum polarization state is spectrally analyzed with optical filters. The method can be extended to other kinds of cylindrical vector beams. Abstract: Spectral broadening of a radially polarized (RP) pulse in a gas-filled hollow-core fiber (HCF) is experimentally studied. Broad spectrum covering from 540 nm to 1070 nm is obtained. It is found that the output spectrum preserves the RP state after nonlinear propagation in HCF, both for the components in the input pulse and for the newly generated spectral portion. This method shows great potential in generating RP sources with unprecedented spectral width, and may also be extended to other kinds of cylindrical vector beams.